2006
DOI: 10.1002/ejic.200600790
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Intercluster Compounds Consisting of Gold Clusters and Keggin Anions

Abstract: 3-were synthesized as single-crystals by a diffusion method. Depending on the solvent combination, two modifications with different core geometries of the gold cluster and different overall packing type can be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
91
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(100 citation statements)
references
References 34 publications
8
91
0
1
Order By: Relevance
“…The borohydride reduction of monophosphine gold(I) complex (Au(PR 3 )X) in ethanol is the original recipe and has been most widely used as a conventional method, which generally yields Au 9 [27,37,38,61,62] or Au 11 species [19,[44][45][46][47][48][63][64][65]. NaBH 4 is commonly exploited as the reducing agent, because of the ease in handling.…”
Section: Borohydride or Borane Reduction Of Gold(i) Phoshine Complexmentioning
confidence: 99%
“…The borohydride reduction of monophosphine gold(I) complex (Au(PR 3 )X) in ethanol is the original recipe and has been most widely used as a conventional method, which generally yields Au 9 [27,37,38,61,62] or Au 11 species [19,[44][45][46][47][48][63][64][65]. NaBH 4 is commonly exploited as the reducing agent, because of the ease in handling.…”
Section: Borohydride or Borane Reduction Of Gold(i) Phoshine Complexmentioning
confidence: 99%
“…For instance, well-formed crystals of [Au 9 (PPh 3 ) 8 ](NO 3 ) 3 can be obtained reliably by reducing [Au(PPh 3 )NO 3 ] with NaBH 4 in ethanol, followed by purification and crystallization from diluted solutions [9]. The cluster cation [Au 9 (PPh 3 ) 8 ] 3+ can be crystallized in two conformations of the gold polyhedron, the so-called crown structure and the butterfly structure [10,11]. It was found that [Au 9 (PPh 3 ) 8 ](NO 3 ) 3 in its butterfly conformation shows luminescence in the near infrared (NIR) in the solid state, which is advantageous for biomedical imaging [9].…”
Section: Introductionmentioning
confidence: 99%
“…These novel ionic crystals, arising from investigations by Jansen and Schulz-Dobrick, have brought about a renaissance in the chemistry of these long-known gold clusters. [16] Depending on the crystallization conditions, either orange-red needles or black-green platelets and prisms are formed, which differ structurally in the Au 9 skeleton and in the crystal packing. Figure 1 shows the crystal structure of the orange-red form, which can be derived from the CsCl structure.…”
mentioning
confidence: 99%